Integrating sustainability and least cost path analysis with a relative sustainability scoring index for optimal road planning - Ahmed K. Samy; Emad S. Bakhoum; Yasmeen A. S. Essawy; Khaled A. Hamdy (Scientific Reports)
Abstract Achieving sustainability in road construction is increasingly critical, yet traditional methods often focus solely on economic factors, creating a significant research gap in the holistic assessment of the three pillars of sustainability: economic, social, and environmental. The purpose of this research is to develop a ‘Relative Sustainability Scoring Index’ (RSSI) that addresses this gap. The research motivation stems from the need for a comprehensive tool that aligns with defined sustainability criteria. Therefore, it aims to quantitatively evaluate road projects, enabling a more robust understanding of the sustainability implications associated with various route planning strategies. The methods employed include the simple additive weight method, informed by expert input through fuzzy logic, and the application of Least Cost Path Analysis in QGIS to generate a suggested route. Civil 3D was utilized for road design and economic analysis, while VISSIM simulated traffic factors, and Simapro assessed environmental impacts. The results indicate that the suggested road achieved a sustainability score of 0.94, surpassing the present road’s score of 0.77. This research helps to improve the decision-making process by providing decision-makers with a quantitative tool that holistically evaluates roads based on economic viability, social acceptability, and environmental impact, thus advancing sustainable road network planning.